Antihypertensive and antiproteinuric efficacy of ramiprilin children with chronic renal failure - Wühl, Elke; Mehls, Otto; Schaefer, Franz (Kidney international, 2004)
Antihypertensive and antiproteinuric efficacy of ramipril in children with chronic renal failure. - Background - While the antihypertensive and renoprotective potency of angiotensin-converting enzyme (ACE) inhibitors is well-established in adults with hypertension and/or chronic renal failure, little experience exists in pediatric chronic kidney disease.
Available online 16 December 2015
Elektronische Reproduktion der Druck-Ausgabe
ESCAPE trial participants are as follows: A. Anarat (Adana); A. Bakkaloglu, F. Ozaltin (Ankara); A. Peco-Antic (Belgrade); U. Querfeld, J. Gellermann (Berlin); P. Sallay (Budapest);D. Drozdz (Cracow); K.-E. Bonzel, A.-M.Wingen (Essen); A. Zurowska, I. Balasz (Gdansk); F. Perfumo, A. Canepa (Genoa); D.E. Müller-Wiefel, K. Zepf (Hamburg); G. Offner, B. Enke (Hannover); O. Mehls, F. Schaefer, E.Wühl, C. Hadtstein (Heidelberg); U. Berg, G. Celsi (Huddinge); S. Emre, A. Sirin, I. Bilge (Istanbul); S. C¸ aliskan (Istanbul-Cerrahpasa); S. Mir, E. Serdaroglu (Izmir); C. Greiner, H. Eichst¨ adt, S. Wygoda (Leipzig); K. Hohbach-Hohenfellner (Mainz); N. Jeck, G. Klaus (Marburg); A. Appiani, G. Ardissino, S. Testa (Milano); G. Montini (Padova); P. Niaudet, M. Charbit (Paris); J. Dusek (Prague); A. Caldas-Afonso, A. Teixeira (Porto); S. Picca, C. Matteucci (Rome); M. Wigger (Rostock); M. Fischbach, J. Terzic (Strasbourg); J. Fydryk, T. Urasinski (Szezecin); R. Coppo, L. Peruzzi (Torino); A. Jankauskiene (Vilnius); M. Litwin, M. Abuauba, R. Grenda (Warszawa); K. Arbeiter (Vienna); T.J. Neuhaus (Zurich)
Gesehen am 19.01.2021